2021
DOI: 10.1038/s41598-021-00831-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chemotherapy for malignant pleural mesothelioma according to histology in a real-world cohort

Abstract: CheckMate 743 trial demonstrated survival benefit of immunotherapy in first line in MPM with some differences in the efficacy of chemotherapy according to histology. The objective of this study is to characterize the impact of chemotherapy according to histology in patients diagnosed with MPM at our institution. Clinical records of all MPM patients diagnosed at Vall d’Hebron University Hospital between November 2002 and April 2020 were reviewed. Associations between clinical variables and outcomes were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Previous studies have reported that the histological type is an important factor affecting the survival time, and the prognosis of MMe patients with epithelial histological type is better than the non-epithelial type (43)(44)(45)(46)(47). Similarly, our study also found that the survival outcomes of MMe patients were closely related to their tissue type.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported that the histological type is an important factor affecting the survival time, and the prognosis of MMe patients with epithelial histological type is better than the non-epithelial type (43)(44)(45)(46)(47). Similarly, our study also found that the survival outcomes of MMe patients were closely related to their tissue type.…”
Section: Discussionsupporting
confidence: 83%
“…Cedres et al evaluated, in a retrospective cohort of 189 patients, systemic therapy outcomes according to histology (26). The study was focused on chemotherapy, confirming better results in terms of OS and PFS in epithelioid than in non-epithelioid tumors in first line setting (26.7 vs 15.0 months for OS, p<0.001, respectively; 4.8 vs 3.6 months for PFS, p=0.03, respectively).…”
Section: Histologymentioning
confidence: 92%
“…• Data about response according to histology are mostly not reported or too small to draw definitive conclusions (6,8,11,13,18,19,26).…”
Section: Histologymentioning
confidence: 99%
“…MPM has an extremely short survival rate, about 8 to 14 months following diagnosis ( 83 ). Histological subtype in MPM has been widely recognized as a prognostic factor, with non-epithelioid histology considered as a predictor of poor survival in two main prognostic scores [European Organization for Research and Treatment of Cancer (EORTC); Cancer and Leukemia Group B (CALGB)] ( 73 ). Furthermore, biphasic forms of non-epithelioid mesothelioma can exhibit a variable percentage of epithelioid differentiation.…”
Section: Differences Between Ar-mpm and Non-ar-mpmmentioning
confidence: 99%